Zolpidem Activation of Alpha 1-Containing GABAA Receptors Selectively Inhibits High Frequency Action Potential Firing of Cortical Neurons - Neumann, Elena; Rudolph, Uwe; Knutson, Daniel E.; Li, Guanguan; Cook, James M.; Hentschke, Harald; Antkowiak, Bernd; Drexler, Berthold (Frontiers in Pharmacology, 2019)
Introduction: High frequency neuronal activity in the cerebral cortex can be induced by noxious stimulation during surgery, brain injury or poisoning. In this scenario, it is essential to block cortical hyperactivity to protect the brain against damage, e.g. by using drugs that act as positive allosteric modulators at GABAA receptors. Yet, cortical neurons express multiple, functionally distinct GABAA receptor subtypes. Currently there is a lack of knowledge which GABAA receptor subtypes would be a good pharmacological target to reduce extensive cortical activity. Methods: Spontaneous neuronal activity was monitored by performing extracellular recordings from organotypic neocortical slice cultures of wild type and GABAAR-alpha1(H101R) mutant mice. Phases of high neuronal activity were characterized using peri-event time histograms. Comparison of neuronal activity was performed by Hedges’g. Results: We quantified the effects of zolpidem, a positive modulator of GABAA receptors harboring alpha1-subunits, and the experimental benzodiazepine SH-053-2’F-S-CH3, which preferably acts at alpha2/3/5- but spares alpha1-subunits. Both agents decreased spontaneous action potential activity but altered the firing patterns in different ways. Zolpidem reduced action potential firing during highly active network states. This action was abolished by flumazenil, suggesting that it was mediated by benzodiazepine-sensitive GABAA receptors. SH-053-2’F-S-CH3 also attenuated neuronal activity, but unlike zolpidem, failed to reduce high frequency firing. To confirm that zolpidem actions were indeed mediated via alpha1-dependent actions, it was evaluated in slices from wild type and alpha(H101R) knock-in mice. Inhibition of high frequency action potential firing was observed in slices from wild type but not mutant mice. Conclusions: Our results suggest that during episodes of scarce and high neuronal activity action potential firing of cortical neurons is controlled by different GABAA receptor subtypes. Exaggerated firing of cortical neurons is reduced by positive modulation of alpha1-, but not alpha2/3/5-subunit containing GABAA receptors.